2017
DOI: 10.21767/2471-8165.1000055
|View full text |Cite
|
Sign up to set email alerts
|

Cesarean Section: Incidence, Causes, Associated Factors and Outcomes: A National Prospective Study from Jordan

Abstract: Objectives: To determine the rate of cesarean section (CS) in Jordan and its causes, associated factors, and neonatal outcomes. Methods:The study is part of a comprehensive national study of perinatal mortality which was conducted between 2011 and 2012 in Jordan. The study was concurrent prospective in design. A sample of 18 hospitals with maternity departments was selected. All women ≥ 20 weeks of gestation admitted for delivery in any of the 18 selected hospitals were enrolled in the study. Data were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
15
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 16 publications
8
15
2
Order By: Relevance
“…Whereas consistent high rates up to100% were observed in some areas (11,13,18,19) lower rates were recorded in others. (10,13,21) Similar to earlier reports (4,7,8,11,18,21) CD was significantly linked to private health services in our univariate and multivariate analysis. Some authors suggested that the rising rate of the planned CD in private sector is due to unnecessary CS and not to increasing obstetric risk.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Whereas consistent high rates up to100% were observed in some areas (11,13,18,19) lower rates were recorded in others. (10,13,21) Similar to earlier reports (4,7,8,11,18,21) CD was significantly linked to private health services in our univariate and multivariate analysis. Some authors suggested that the rising rate of the planned CD in private sector is due to unnecessary CS and not to increasing obstetric risk.…”
Section: Discussionsupporting
confidence: 91%
“…(1,4,20) In consistence, previous CD was the leading indication of CD in the present as well in previous Egyptian (7,(14)(15)(16)(17) and non-Egyptian studies . (3,4,10,12,21,22) Also, previous CS was a main predictor for CS in the present and similar studies. (10,19) Moreover, Witt et al elicited that having earlier CS was the strongest predictor of non-indicated CS .…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations